Selection of rhizobia due to their effect on germination and incipient development of Moringa oleifera Lam. Phase I: controlled conditions - Becquer, C. J.; Cancio, T.; Muir, Ivón; Ávila, U.; Álvarez, Orquidea; Madrigal, Yahima (Cuban Journal of Agricultural Science, 2018)
An assay was conducted under controlled conditions to evaluate the effect of different native isolates and reference strains of rhizobia on agro-physiological variables of Moringa oleifera Lam., as well as to select the best treatments for their evaluation in greenhouse or nursery. A completely randomized design with 12 treatments and14 repetitions ws applied, an ANOVA analysis was performed. Differences between means were determined by Fisher LSD test. The values with digit counting were transformed by √x, and the percentage data by arcosen√P. Correlation coefficient among variables was calculated. It is concluded that isolates JK5, Ho9 andHo5 exerted a positive superior effect on germination at 10 and 15 days after sowing, as well as in most of the variables. However, the reference strains showed an efficiency index of inoculation in dry weight of the aerial part, lower than that of native isolates. The 50 % of the treatments inoculated presented values superior to the absolutecontrol in dry weight of the aerial part and in dry weight of the root, as well as superior to the control fertilized in this last variable. On the other hand, nitrogen fertilization did not show a positive effect on any of the evaluated variables. It is noteworthy that there was a moderately strong statistical correlation between dry weight ofthe root and dry weight of the aerial part, as well as between dry weight of the aerial part and index of germination speed, which indicates a high physiological interrelation among these variables. It is recommended to carry out greenhouse or nursery phase tests with the isolates Ho4, JK5 and Ho9.Key words: Moringa oleifera, rhizobia, agro-physiological variables